Beyond the Crystal Structure: Insight into the Function and Vaccine Potential of TbpA Expressed by Neisseria gonorrhoeae - Cash, Devin R. (Infect Immun, 2015)
Neisseria gonorrhoeae, the causative agent of the sexually transmitted infection gonorrhea, is not preventable by vaccination and is rapidly developing resistance to antibiotics. However, the transferrin (Tf) receptor system, composed of TbpA and TbpB, is an ideal target for novel therapeutics and vaccine development. Using a three-dimensional structure of gonococcal TbpA, we investigated two hypotheses, i.e., that loop-derived antibodies can interrupt ligand-receptor interactions in the native bacterium and that the loop 3 helix is a critical functional domain. Preliminary loop-derived antibodies, as well as optimized second-generation antibodies, demonstrated similar modest ligand-blocking effects on the gonococcal surface but different effects in Escherichia coli. Mutagenesis of loop 3 helix residues was employed, generating 11 mutants. We separately analyzed the mutants' abilities to (i) bind Tf and (ii) internalize Tf-bound iron in the absence of the coreceptor TbpB. Single residue mutations resulted in up to 60% reductions in ligand binding and up to 85% reductions in iron utilization. All strains were capable of growing on Tf as the sole iron source. Interestingly, in the presence of TbpB, only a 30% reduction in Tf-iron utilization was observed, indicating that the coreceptor can compensate for TbpA impairment. Complete deletion of the loop 3 helix of TbpA eliminated the abilities to bind Tf, internalize iron, and grow with Tf as the sole iron source. Our studies demonstrate that while the loop 3 helix is a key functional domain, its function does not exclusively rely on any single residue.